Efficient electrocatalytic reduction of CO2 on an Ag catalyst in 1-ethyl-3-methylimidazolium ethylsulfate, with its co-catalytic role as a supporting electrolyte during the reduction in an acetonitrile medium - Muhammad, Sayyar; Ali, Asad (Frontiers in Chemistry, 2025)
CO2 electrochemical reduction reactions (CO2ERR) has shown great promise in reducing greenhouse gas emissions while also producing useful chemicals. In this contribution, we describe the CO2ERR at different catalysts using 1-ethyl-3-methylimidazolium ethyl sulfate [emim][EtSO4] ionic liquid (IL) as a solvent and as a supporting electrolyte. CO2ERR occurs at Ag and Cu catalysts at a lower overpotential than that at Au, Pt, and boron-doped diamond (BDD) catalysts. In addition, we report that ILs play a better co-catalytic role when used as a supporting electrolyte during CO2ERR in an acetonitrile (AcN) medium than the conventional supporting electrolyte, tetrabutylammonium hexafluorophosphate [TBA][PF6] in AcN. Furthermore, it is found that imidazolium-based cations ([emim]+) play a significant co-catalytic role during the reduction compared to [TBA]+ and pyrrolidinium [empyrr]+ cations, while anions of the ILs play no such role. The formation of CO from the CO2ERR was detected using cyclic voltammetry at an Ag catalyst both in [emim][EtSO4] as well as in an AcN solvent containing [emim][EtSO4] as a supporting electrolyte. The product of the CO2 reduction in this IL medium at the Ag catalyst is CO, which can be converted to synthetic liquid fuels by coupling the process with the Fischer–Tropsch process or through the conversion of CO2 into fuels based on green hydrogen by the Sabatier process, that is, methanation of CO2 on industrial scale, in the future.